Virtual reality and 21st century education - Rivas, Yeneri Carolina; Valdivieso, Patricio Alfredo Vallejo; Rodriguez, Marcos Alejandro Yanez (International research journal of management, IT and social sciences, 2020)
Virtual Reality (RV), is one of the technological tools of the 21st century applied in the field of education and has increased significantly the use of it, to achieve the expected learning in students, the present This article aimed to demonstrate that VR as an innovative tool in 21st-century education contributes significantly to the teaching-learning process of students and teachers. It has worked based on a descriptive methodology-documentary, applying the analysis and interpretation of content, was limited to the review of articles published in digital journals, located in different databases, among the results there is a challenge that education should Assume and actively incorporate virtual reality, such as the technology that is a fundamental part of the daily life of the new generations, as an educational paradigm focused on the student, where it is intended to be autonomous and independent in the generation of learning.